Spirituality, integrity and counterproductive work behaviours among employees of selected Islamic organisations in Malaysia - Hashim, Junaidah (2013)
This research examines the mediating effect of integrity on spirituality and organisation performance. A total of 1203 employees responded to the survey. Measures used were Human Spirituality Scale (Wheat, 1991), workplace spirituality (Petchsawang and Duchon, 2009), counterproductive work behaviour (Gruys and Sackett, 2003), and the Substance, Production loss, and Interpersonal Problem Inventory (SPI). The findings failed to support the hypothesised model.